Doppler velocimetry and adverse outcome in labor induction for late IUGR. (1st February 2017) - Simeone, Serena; Marchi, Laura; Canarutto, Rita; Pina Rambaldi, Marianna; Serena, Caterina; Servienti, Cristina; Mecacci, Federico
Abstract: Background : Late onset intrauterine growth restriction (IUGR) represents one of the main causes of perinatal morbidity/mortality. No guidelines are available on labor induction in IUGRs, even if delivery at 37/38 weeks is suggested. This study aims to assess maternal–fetal variables related to adverse outcome in labor induction for late IUGR. Methods : One hundred cases of induction for late IUGR were retrospectively revised on fetal weight, MCA, UA, CPR and uterine artery (utA) Doppler, oligohydramnios, Bishop score, start of induction, augmentation. The variables were matched with the following adverse outcomes: CS or vacuum extractor delivery (IVD); NICU admission; low Apgar score; UA pH < 7.10. Results : Regular vaginal delivery occurred in 65% of cases; the rate of CS and IVD was 32% and 5%. UA, MCA and CPR abnormalities were all significantly related to a higher risk of CS. Bishop score < 3 and start of induction by oxitocin resulted statistically associated to CS, while prostaglandins were related to vaginal delivery. No augmentation and oxitocin in labor were positively related to vaginal delivery. Maternal morbidity and Bishop score < 3 showed a significant association with NICU admission. Discussion : Doppler velocimetry of UA, MCA and CPR are useful tools for the identification and management of the late term IUGRs.